2000
DOI: 10.1074/jbc.275.14.10604
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Signaling between α6β4Integrin and ErbB-2 Receptor Is Required to Promote Phosphatidylinositol 3-Kinase-dependent Invasion

Abstract: We previously demonstrated that ␤ 4 integrin subunit overexpression increases in vitro invasiveness of NIH3T3 cells that have been transformed by ErbB-2 oncogene. We used this model to identify domains within the large ␤ 4 cytoplasmic domain that are involved in the interaction of ␣ 6 ␤ 4 with ErbB-2, invasion, and phosphatidylinositol 3-kinase (PI3K) activation. For this purpose, we expressed deletion mutants of ␤ 4 that lacked either all or portions of the ␤ 4 cytoplasmic domain in NIH3T3/ErbB-2 cells. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
143
8
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(163 citation statements)
references
References 34 publications
11
143
8
1
Order By: Relevance
“…Effectors of these signaling cascades include MAPK, NFκB, Jun, β-catenin and others and together they modulate cell proliferation, cell survival, cell migration and invasion. Among the mitogenic integrins are α 6 β 4 or α v β 3 -integrins which cooperate with diverse growth factor receptors, including EGFR, ErbB2, and c-Met [108][109][110][111]. On the other hand, growth inhibitory signals can be transmitted, for example via α 2 β 1 -integrin, which in turn activates p38-MAPKmediated cell-cycle inhibition [112,113].…”
Section: Integrin-mediated Cell-matrix Adhesion and Signalingmentioning
confidence: 99%
“…Effectors of these signaling cascades include MAPK, NFκB, Jun, β-catenin and others and together they modulate cell proliferation, cell survival, cell migration and invasion. Among the mitogenic integrins are α 6 β 4 or α v β 3 -integrins which cooperate with diverse growth factor receptors, including EGFR, ErbB2, and c-Met [108][109][110][111]. On the other hand, growth inhibitory signals can be transmitted, for example via α 2 β 1 -integrin, which in turn activates p38-MAPKmediated cell-cycle inhibition [112,113].…”
Section: Integrin-mediated Cell-matrix Adhesion and Signalingmentioning
confidence: 99%
“…These alterations, together with changes in integrin and cadherin function frequently observed in tumor cells with activated HER, facilitate the communication between tumor cells and their escape from control by the microenvironment. In particular, the creation of new interactions of HER family members with integrins, such as HER2 and a 6 b 4 ( Figure 1) and focal adhesion kinases recruits the PI3 K pathway (Campiglio et al, 1994;Tagliabue et al, 1996;Gambaletta et al, 2000), inducing the release of second messengers (phosphoinositides and calcium). These molecules in turn recruit multiprotein complexes that play a role in reorganization of actin cytoskeleton, and thus in tumor cell migration (Dittmar et al, 2002;Feldner and Brandt, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Advances include the observation that ␣ 6 ␤ 4 is localized to the leading edge of migrating carcinoma cells where it can contribute to the formation and stabilization of actin protrusions (16,17). In addition, there is evidence from several laboratories indicating that ␣ 6 ␤ 4 stimulates the activity of phosphoinositide 3-OH kinase (PI3K) 1 in invasive carcinoma cells and that PI3K is essential for migration and invasion (7,18). Interestingly, it has been suggested that ␣ 6 ␤ 4 activates PI3K and mediates invasion through its ability to cooperate with specific growth factor receptors (1,4,18).…”
mentioning
confidence: 99%